2014
DOI: 10.1002/2013jg002552
|View full text |Cite
|
Sign up to set email alerts
|

Scales and drivers of temporal pCO2 dynamics in an Alpine stream

Abstract: The role of inland waters for the global carbon cycle is now recognized and evidence increasingly suggests that stream ecosystems disproportionately contribute to the carbon cycle. Understanding the dynamics and drivers of stream water partial pressure of CO 2 (pCO 2 ) and CO 2 evasion fluxes from streams to the atmosphere is imperative for assessing the role of climate change on the carbon cycle in stream ecosystems. Monitoring pCO 2 over 3 years, we here report on the seasonal, diurnal, and event-driven dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
114
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 102 publications
(146 citation statements)
references
References 62 publications
24
114
2
Order By: Relevance
“…The simulated result showed annual-averaged evasion flux during night exceeded that during day by up to 1.17 times at most in Africa (Fig.6c). This value was smaller than the previous measurement in temperate region (Peter et al, 2014), which showed averaged evasion flux during night exceeded that during day by up to 1.8 times. However, in local scale, the simulated evasion flux during night exceeded that during day 10 by up to 1.43, 3.92, and 1.76 times temporarily in summer in Ob, Yangtze, and Mekong Rivers (Figs 4d-f).…”
contrasting
confidence: 77%
See 4 more Smart Citations
“…The simulated result showed annual-averaged evasion flux during night exceeded that during day by up to 1.17 times at most in Africa (Fig.6c). This value was smaller than the previous measurement in temperate region (Peter et al, 2014), which showed averaged evasion flux during night exceeded that during day by up to 1.8 times. However, in local scale, the simulated evasion flux during night exceeded that during day 10 by up to 1.43, 3.92, and 1.76 times temporarily in summer in Ob, Yangtze, and Mekong Rivers (Figs 4d-f).…”
contrasting
confidence: 77%
“…storage decreases in nighttime (Figs 4d-f), in particular, in Asia and Africa (CO2 evasion increase and sediment storage decrease are 6.35 and 1.32 TgC/yr in Asia, and 5.67 and 0.73 TgC/yr in Africa, respectively). This result also suggests clearly that measurement pCO2 during daytime only, in most of previous observation data, might seriously underestimate annual averages of CO2 outgassing fluxes from inland water to the atmosphere (Peter et al, 2014), and that it is necessary to observed pCO2 during nighttime furthermore not only in local scale but also in regional scale. 5…”
Section: Impact Of Regional Hot Spots On Global Carbon Cycle Changementioning
confidence: 76%
See 3 more Smart Citations